2012
DOI: 10.1038/ejhg.2012.18
|View full text |Cite
|
Sign up to set email alerts
|

Direct-to-consumer genomic testing: systematic review of the literature on user perspectives

Abstract: Genetic tests have traditionally been offered by health professionals. However, genomic tests have been available direct to the consumer for the last decade, increasingly via the Internet. The aim of this systematic review was to ascertain the evidence concerning use of direct-to-consumer genomic testing from the consumer perspective. Primary research was identified using the search terms 'direct-to-consumer' and 'genomic or genetic' in six bibliographic databases and citation searching of findings. In all, 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 31 publications
4
83
0
4
Order By: Relevance
“…The key reasons for potentially undergoing DTC genomic testing in this study population was the opportunity for research participation as well as receiving information about health and personal traits. These findings are similar to other studies [9], although it is of particular interest that in our sample research participation was highly ranked. The research participation motive was mostly chosen by science/engineering and medical students.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The key reasons for potentially undergoing DTC genomic testing in this study population was the opportunity for research participation as well as receiving information about health and personal traits. These findings are similar to other studies [9], although it is of particular interest that in our sample research participation was highly ranked. The research participation motive was mostly chosen by science/engineering and medical students.…”
Section: Discussionsupporting
confidence: 92%
“…In the case of good news, other issues surfaced, such as those about the nature of the tests and their low clinical utility. Other studies, however, that have examined experiences of actual test-takers show that users are unlikely to act on the results they receive through DTC testing, even if at the time of testing they intended to act [9,21]. It is unclear why DTC genomics results do not seem to have either a positive (or negative) effect on actions about health [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ignorance about the fact that DNA is beneficial to the generation of PN might have lowered the perception of personalisation benefit. In addition to perceiving DNA as not beneficial to PN, and consistent with studies into consumer attitudes [41,42,43], disclosing DNA to a PN service was identified as a factor that increases privacy risk. Participants, for example, mentioned that DNA should not fall into the wrong hands, either when disclosing it to the PN service or when it is already made available to the PN service for the purpose of PN advice generation (stages 1 and 2 of the PN information exchange process).…”
Section: Discussionmentioning
confidence: 52%
“…The attack process is similar to existent direct-to-consumer health-related genetic profiling [13], which informs about an individual's probabilities of contracting a disease or any other gene-related information. These tests do not provide diagnosis, but in the wrong hands, they still may cause harm to a victim's reputation or otherwise disadvantage her.…”
Section: Attackmentioning
confidence: 99%